(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, it is emphasized that family and marriage have been considered a sacred Motherland in our country since ancient times. It is stated that the factors that make changes in Uzbek marriage ceremonies are the desire for a modern lifestyle and changes in society, in particular, the deepening of the market economy.